Changing from Standard Form to Slope-Int Form

The slope-intercept form The slope-intercept form y = mx + b The slope-intercept form y = mx + b always has y... The slope-intercept form y = mx + b always has y... ...absolutely... The slope-intercept form y = mx + b always has y... ...absolutely... ...totally... The slope-intercept form y = mx + b always has y... ...absolutely... ...totally... ...all by itself. The slope-intercept form y by itself y = mx + b always has y... ...absolutely... ...totally... ...all by itself. The standard form The standard form Ax + By = C The standard form Ax + By = C always has... The standard form Ax + By = C always has... x and y on one side, x and y on one side The standard form Ax + By = C always has... x and y on one side, The standard form Ax + By = C and everything else on the other side always has... x and y on one side, The standard form Ax + By = C and everything else on the other side always has... x and y on one side, everything else 2x + 3y = 4 Standard ? Match the equation with its form. Slope-intercept ? y = 2x + 5 an equation To change any equation x + y = 5 To change any equation x + y = 5 into slope intercept form To change any equation x + y = 5 into slope intercept form y = mx + b To change any equation x + y = 5 into slope intercept form y = mx + b you have to get y by itself This y needs to be alone To change any equation x + y = 5 into slope intercept form y = mx + b you have to get y by itself To do this we use Algebra To do this we use Algebra x + y = 5 To do this we use Algebra x + y = 5 we need to get y by itself so we need to get rid of the x To do this we use Algebra x + y = 5 we need to get y by itself To do this we use Algebra -x x + y = 5 -x subtract x on both sides To do this we use Algebra -x x + y = 5 -x subtract x on both sides to get rid of the x To do this we use Algebra x - x cancels -x x + y = 5 -x subtract x on both sides to get rid of the x To do this we use Algebra x - x cancels Leaving just y on that side -x x + y = 5 y = -x subtract x on both sides to get rid of the x To do this we use Algebra are not like terms since 5 and -x -x x + y = 5 y = -x subtract x on both sides to get rid of the x we can't add them To do this we use Algebra are not like terms since 5 and -x -x x + y = 5 y = -x subtract x on both sides to get rid of the x we can't add them To do this we use Algebra are not like terms since 5 and -x -x x + y = 5 y = -x + 5 -x leaving us with this subtract x on both sides to get rid of the x To do this we use Algebra The y is by itself now -x x + y = 5 y = -x + 5 -x To do this we use Algebra so this equation is in slope-intercept form The y is by itself now -x x + y = 5 y = -x + 5 -x standard equation We changed this x + y = 5 y = -x + 5 standard equation We changed this x + y = 5 y = -x + 5 slope-intercept equation into this Match the equation with its form 6x - 2y = 12 Standard ? Slope-intercept ? y = 4x Match the equation with its form Slope-intercept ? y = 3x + 1 -4x - y = 4 Standard ? Match the equation with its form x + y = 5 Standard ? Slope-intercept ? y = x + 5 Match the equation with its form Slope-intercept ? y = -2x - 4 x - 5y = 9 Standard ? Which equation is equivalent to 4x - 3y = 9? y = -4x + 9 y = 4/3x - 3 y = -4/3x - 3 y = -3/4x - 3 Which equation is equivalent to x + 3y = -6? y = -1/3x - 2 y = -3x - 3 y = -3x - 2 y = -x - 6 Which equation is equivalent to 2x - y = 8? y = -x + 4 y = -2x + 8 y = 2x + 4 y = 2x - 8 Which equation is equivalent to y = 3x - 1? 6x - 2y = 2 3x + y = 1 -3x - y = 1 6x + 2y = 2 In changing from standard form to slope-intercept form, what should be your first step? Find slope Divide by the y-coefficient Add or Subtract the "Ax" term Divide each side by the "Ax" term |

Students who took this test also took :

Created with That Quiz —
where test making and test taking are made easy for math and other subject areas.